Demographic Profiling and the Organizational Citizenship Behaviour A Study among the Graduate Trainees in Batticaloa District of Sri Lanka - Selvarajan, P.; Sreepriya, S. (Faculty of Management Studies, Rajarata University of Sri Lanka, 2021)
: The Sri Lankan government has executed a programme island-wide for the placement of 50,000 Unemployed Graduates for the first time with effect from September 2020. Past literature proved that there is a relationship between the demographic profile of employees and their Organizational Citizenship Behaviour (OCB). However, a previous study of the researchers on OCB of Graduate Trainees in Batticaloa District revealed a positive relationship, job satisfaction, task interdependence, and public service motivation excluding the demographic factors. The objective of the present study is to investigate the influence of different demographic factors- gender, age, and prior experience on the OCB of graduate trainees in Batticaloa District of Sri Lanka. The study was carried out with a multi-stage sampling method by selecting a sample of 150 from the total population of 441 graduate trainees in Batticaloa. The result of the independent samples t-test shows that no significant difference in terms of OCB between male and female graduates. A one-way ANOVA test indicates that the independent variable age has not significantly influence and concludes that there is no mean difference in terms of OCB between various age groups of graduate trainees in the Batticaloa district. The third independent variable indicates that there is no difference among the OCB of graduate trainees with prior experience. The study concludes that factors such as age, gender and prior experience do not cause any difference in the OCB of graduate trainees in the Batticaloa district. The current study provides insights to understand the influence of demographic factors on the OCB of Graduate Trainees which would enable the policymakers and other stakeholders when making decisions in the future as well.
Keywords: Age; gender; Organizational citizenship behaviour; Prior experience